2014
DOI: 10.1109/tap.2014.2363681
|View full text |Cite
|
Sign up to set email alerts
|

On the Analogy Between Vehicle and Vehicle-Like Cavities With Reverberation Chambers

Abstract: Deploying wireless systems in vehicles is an area of current interest. Often, it is implicitly assumed that the electromagnetic environment in vehicle cavities is analogous to that in reverberation chambers, it is therefore important to assess to what extent this analogy is valid. Specifically, the cavity time constant, electromagnetic isolation and electric field uniformity are investigated for typical vehicle and vehicle-like cavities. It is found that the time constant is a global property of the cavity (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…First, we use the reverberation chamber to verify an important assumption, specifically that the time variation can be considered to be a WSSUS process. Secondly, in a metal cavity which has been verified to have vehicle-like properties [3], [11], this metal cavity was placed in a fully anechoic chamber that allowed us to perform tightly controlled measurements, having a very low noise floor (i.e., the anechoic chamber is shielded from external radiation, so only thermal noise is present). Finally, measurements were performed in an actual vehicle, which enabled us to measure the ground truth.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we use the reverberation chamber to verify an important assumption, specifically that the time variation can be considered to be a WSSUS process. Secondly, in a metal cavity which has been verified to have vehicle-like properties [3], [11], this metal cavity was placed in a fully anechoic chamber that allowed us to perform tightly controlled measurements, having a very low noise floor (i.e., the anechoic chamber is shielded from external radiation, so only thermal noise is present). Finally, measurements were performed in an actual vehicle, which enabled us to measure the ground truth.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Before enumerating these causes we note that it has been shown that external objects have little influence on the propagation process in the vehicle cavity [3]. The primary causes of time variation are:…”
Section: A Causes Of Channel Variation With Timementioning
confidence: 99%
See 3 more Smart Citations